Development of infrared fiber lasers at 1555 nm and at 2800 nm based on Er-doped zinc-tellurite glass fiber - Anashkina, E. A.; Andrianov, A. V.; Dorofeev, V. V.; Kim, A. V.; Koltashev, V. V.; Leuchs, Gerd; Motorin, S. E.; Muravyev, S. V.; Plekhovich, A. D. (Journal of Non-Crystalline Solids, 2019)
We manufactured and characterized a low-loss gain fiber based on high-purity TeO2–ZnO–La2O3–Na2O undoped glass for 100-μm cladding and TeO2–ZnO–La2O3–Na2O glass for 10-μm core doped with 0.24 mol% Er2O3. To confirm that the produced fiber is a promising active element for the infrared range, we demonstrated experimentally broadband laser amplification and CW generation at the 4I13/2 → 4I15/2 transition at 1555 nm with a single-mode diode pump at 975 nm at the 4I15/2 → 4I11/2 transition. We developed a numerical model calibrated to the experimental data for prediction and optimization of laser characteristics in schemes with different parameters. The model describes single- wavelength lasing as well as dual-wavelength cascade lasing at 1555 nm and 2800 nm. It was shown numerically that for the optimized parameters, the maximum slope efficiency at 2800 nm at the 4I11/2 → 4I13/2 transition can reach 20%. The maximum calculated efficiency at 1555 nm exceeds 30%.
CRIS-Team Scopus Importer:2023-04-20